Determinan Fenomena Middle Income Trap Delapan Negara Berpendapatan Menengah di Kawasan ASEAN Tahun 2009-2019 - Lisayoana, Jasika; Tasriah, Etjih (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2024)
The middle-income trap (MIT) is an economic situation where a middle-income country experiences stagnation, making it difficult to advance to a higher income level. The Association of Southeast Asian Nations (ASEAN) is a region where eight out of ten countries are classified as middle-income. Although ASEAN's economic growth rate has been relatively stable, averaging 5–6 percent, the growth of its middle-income economies has shown a tendency to slow. When economic growth is slow and productivity is low relative to available factors of production, a country struggles to boost its economy. This research aims to identify the factors influencing the MIT phenomenon in ASEAN's middle-income countries using a panel data regression model. The results indicate that Foreign Direct Investment (FDI), the Human Development Index (HDI), the output share of the service industry, and the Open Unemployment Rate (TPT) significantly affect the MIT index. In contrast, the output share of the manufacturing industry was found to have no significant effect. It is hoped that this research will contribute to helping middle-income economies in the ASEAN region avoid the middle-income trap.